Sign language students in hearing fieldwork practice: experiences from a Norwegian bachelor program in learning disability nursing - Moradi, Shahram; Vikholt, Steinar; Møller-Skau, Christian; Strøm, Maiken Sudmann; Langemyhr, Lise Ellingsen; Braathen, Tore Norendal (Frontiers in Education, 2026)
PurposeThis study explores the experiences of sign language students during fieldwork practice in learning disability nurse education within predominantly hearing clinical settings.MethodsSemi-structured interviews were conducted with five sign language students and three fieldwork supervisors.ResultsTwo overarching themes emerged: “responsibility for accommodations is placed mainly on the shoulders of the students” and “communication is more demanding for all parties.” While students reported positive aspects of their fieldwork experiences, they also described challenges such as coordinating interpreters, insufficient interpreter support during evenings and weekends, fatigue from noisy environments, and limited deaf awareness among staff. Supervisors highlighted the need for better pre-placement preparation. Communication barriers affected everyone involved and were closely linked to practical accommodations for fieldwork practice.DiscussionThe findings highlight the importance of proactive pre-placement planning, consistent use of qualified interpreters, and deaf awareness training for supervisors and staff to ensure inclusive and equitable fieldwork experiences for sign language students in professional education.